Proposta de índice padrão para o setor de serviços médicos hospitalares e análises clínicas e diagnósticos de companhias listadas na B3 - Santos, Adriano Ferreira dos (2021)
This research aimed to assess all companies listed on the Stock Exchange - B3, in the Hospital Medical Services, Clinical Analysis and Diagnostics sector, and in general, evaluate the income statements for the year 2019 and calculate financial indicators. The main goal of the research was, based on the financial indicators, to elaborate a Standard Index for each one of them, to set a comparison with the indicators of health operators in Brazil and, according to the outcomes, to answer the research problem: How is the financial health of companies in the Hospital Medical Services, Clinical Analysis and Diagnostics sector and if they are in accordance with the literature in the survey. For the theoretical framework, Brazil’s health system was researched in a way which covers the public and private fields, companies listed on the stock exchange and calculations of the proposed indicators. The methodology was bibliographical and exploratory, which explain how the standard index was built. As a result of the research, none of the companies has the chance of a possible bankruptcy, in all the elaborated indexes the companies present good performance. Finally, the research aimed at new studies for application in other sectors of Brazilian economy, and new comparisons with other business performance indicators